LINEAR CONGRUENT METHOD (LCM) IN TESTING SYSTEM USING CLIENT-SERVER MODEL - Basri Basri; Muhammad Assidiq; Uni Anatasya (IJISCS (International Journal of Information System and Computer Science), 2018)
This study aims to apply the Linear Congruent Method (LCM) method using client-server test system, so as to minimize the weakness of examining process and the teacher's mistake in valuation that may occur. LCM method in this research was used to scramble questions data before testing and sent to the Client (Student) by the Server (Teacher) via a TCP/IP Socket. The system was designed through the VB.Net Programming Language. The results showed that by implementing LCM method in test system lead to 100% performance